Upaya Penurunan Kadar Kolesterol Dengan Pemberian Susu Kedelai dan Pemanfaatan Senam Kolesterol di Wilayah Batu Besar RT 03 RW 01 Kecamatan Nongsa - Mira Agusthia; Nur Fadhilah; Fitri Juliana; Meilinda Silaban; Puspita Sari; Rahmadillah Muhti; Rehan Tri Natami; Septri Monalisa N (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
Cholesterol is a natural substance that exists in the body, but unfortunately if it is too much in the blood it will cause blockages in the blood vessels. According to the World Health Organization, 17.5 million people worldwide die from coronary heart disease caused by hypercholesterolemia or 31% of the total number of deaths worldwide. Some of the residents of Batu Besar RT 03 RW 01 said and acknowledged that there are some residents who are still neglectful of high cholesterol levels which cause several health problems so that regular cholesterol exercise can reduce blood cholesterol levels. If cholesterol levels fall, it is very good for the body because it can prevent us from the risk of cardiovascular disease. Soybean contains protein, fiber, isoflavones and lecithin, which can lower cholesterol levels. The purpose of implementing this community service is to reduce cholesterol levels in residents in the Batu Besar Region, RT 03 RW 01, Nongsa District. The method of implementing community service used is providing education, physical activity actions through cholesterol gymnastics and giving soy milk. The result of implementing this community service is that people's knowledge about cholesterol increases and they are able to carry out gymnastics